The Influence of IFRS Convergence on Relevance of Banking Company Accounting Information Value in Indonesia Stock Exchange - Dwily Marlitah Djara (Universitas Pendidikan Ganesha, 2020)
This study aimed to examine whether the convergence of International Financial Reporting Standards (IFRS) increases the value relevance of accounting information as indicated by the book value of equity per share and earnings per share. The population of this study was banking firms listed on the Indonesian Stock Exchange (IDX) in the 2007-2016 period. The hypothesis testing used the dummy regression analysis to test the effect of IFRS convergence. The results show the influence of IFRS convergence on the value relevance of accounting information, as indicated by the increase in the book value of equity per share and earning per share.